Propuesta de diseño arquitectónico y antropométrico Hogar Magnus Senil en Bucaramanga, Santander (2023)
The work of a geriatric home is considered and emphasized in the capacity of comprehensive and professional care that is provided by offering a necessary service at a zonal level to people in elderly condition, which in turn in most cases old age is accompanied by physiological and cognitive diseases.